IMBER – Research for marine sustainability: Synthesis and the way forward. (December 2015) - Hofmann, Eileen; Bundy, Alida; Drinkwater, Ken; Piola, Alberto R.; Avril, Bernard; Robinson, Carol; Murphy, Eugene; Maddison, Lisa; Svendsen, Einar; Hall, Julie; Xu, Yi
Highlights: IMBER advances understanding of end-to-end (physics to top predators) approaches for predicting changes in marine ecosystems. IMBER facilitates comparative studies between diverse systems (polar to tropical) of the global ocean. IMBER undertakes synthesis activities to understand and quantify oceanic carbon uptake, transport, and storage capacity. IMBER developed an integrated assessment framework to triage and facilitate social and governing responses to global marine change. IMBER capacity building activities promote development of ocean-human interaction research. Abstract: The Integrated Marine Biogeochemistry and Ecosystem Research (IMBER) project aims at developing a comprehensive understanding of and accurate predictive capacity of ocean responses to accelerating global change and the consequent effects on the Earth system and human society. Understanding the changing ecology and biogeochemistry of marine ecosystems and their sensitivity and resilience to multiple drivers, pressures and stressors is critical to developing responses that will help reduce the vulnerability of marine-dependent human communities. This overview of the IMBER project provides a synthesis of project achievements and highlights the value of collaborative, interdisciplinary, integrated research approaches as developed and implemented through IMBER regional programs, working groups, project-wide activities, national contributions, and external partnerships. A perspective is provided on the way forward for the next 10 years of the IMBER project as the global environmental change research landscape evolves and as new areas of marine research emerge. IMBER science aims to foster collaborative, interdisciplinary and integrated research that addresses key ocean and social science issues and provides the understanding needed to propose innovative societal responses to changing marine systems.